INDIRECT REFUSAL STRATEGIES IN THE FILM “The Blind Side” - Ansar, Fithrah Auliya (English Education: Jurnal Tadris Bahasa Inggris, 2015)
This research entitled "Indirect Refusal Strategies in The Film "The Blind Side" is a study of indirect refusal in one of drama films. In this research, the researcher chose indirect refusal in her studies due to knowing how people make indirect refusal and the strategies that they use in order to avoid the conflict and not to hurt someone else feeling.The research aims to find out the indirect refusal in the dialogues, in order to understand the better way of people convey their strategy to refuse something with indirect refusal strategies. The second goal is the researcher wants to know about the types of indirect refusal strategies that are used by the main characters in the conversation. In collecting the data, the researcher used two stages in her instrument; the first stage is note taking and the second stage is checking list.            In doing the analysis, the researcher found the answers of these research problems about indirect refusal strategies and the type of indirect refusal strategies in the film “The Blind Side.  The researcher found there are 12 conversations using indirect refusal strategies in the film “The Blind Side”. The researcher also found there are three types of indirect refusal strategies which used in the film “The Blind Side”. The indirect refusal strategies that used in the film “The Blind Side” are the expression of a positive opinion, the expression of regret and the expression of reason.